(untitled) (Veterinary Science, 2017)
The objective of this study is to show new concepts on the repair of bone fractures in dogs through biologic osteosynthesis. Basic principles on regenerative mechanisms, vascularization and osseous stability in fractures of long bones will be depicted. The authors conclude that as long as osteal circulation and surrounding muscles remain intact a desmal callus (made of fibroblast, collagen and cartilage) between osseous terminals is formed developing osteoblasts. With an even and slow tension a primary callus that appears next allows an early limb support